TAMAN MINI KALIMANTAN BARAT DI KUBURAYA - Christian, Vallen; Andi, Uray Fery; Rudiyono, Rudiyono (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2021)
The tourism potential and area of West Kalimantan make it difficult for tourists to enjoy its natural and cultural tourism. The distance is quite far, making it difficult for tourists to share a short time to enjoy all the tours available. When viewed from the potential side, West Kalimantan has advantages such as abundant tourist attractions, culture, ethnicity, and various cultures. With this potential, it is necessary to have a container that can cover all the potential that exists in one area in the form of West Kalimantan Mini Park. The purpose of designing the Mini Park of West Kalimantan is expected to present the religious tourism potential of West Kalimantan in an integrated tourist area in Kubu Raya. The design method used in the design of Taman Mini West Kalimantan refers to 5 stages of design, which will start from the initial stages, preparation, submitting proposals, evaluating, and taking action. The design results are in the form of recreational tourism areas and cultural potential in the form of pavilions that represent districts / cities in West Kalimantan.